2005
DOI: 10.1172/jci23043
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical administration of small interfering RNA targeting PLK-1 successfully prevents the growth of bladder cancer

Abstract: The mainstay in the management of invasive bladder cancer continues to be radical cystectomy. With regard to improvement of quality of life, however, therapies that preserve the bladder are desirable. We investigated the use of intravesical PLK-1 small interfering RNA (siRNA) against bladder cancer. Patients with bladder cancers expressing high levels of PLK-1 have a poor prognosis compared with patients with low expression. Using siRNA/cationic liposomes, the expression of endogenous PLK-1 could be suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(59 citation statements)
references
References 29 publications
3
56
0
Order By: Relevance
“…16 Cationic liposomes were successfully used to deliver siRNA after intravesical administration in the murine bladder. 17 The current study supports the use of cationic liposomes as an OND carrier.…”
Section: Discussionsupporting
confidence: 78%
“…16 Cationic liposomes were successfully used to deliver siRNA after intravesical administration in the murine bladder. 17 The current study supports the use of cationic liposomes as an OND carrier.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, it has previously been reported that gene silencing induced by siRNA/DNA is likely to be less effective than that induced by its unmodified counterparts, because siRNA/DNA exhibits weaker activity for formation of am RNA-induced silencing complex [13,51]. Considering these facts, we adopted a multiple siRNA/ DNA injection protocol (in the present study, thrice, at days 0, 7, and 14) as described elsewhere [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…15,23,2528 UM-UC3 and UC14 have been used with varying success. 25,29,30 Anecdotally we can report that UM-UC3 at one point in our hands was KU7 (and therefore HeLa; true UM-UC3 clones are readily available), and MGHU3 has been shown to be the myeloma cell line KMS-18 (data not shown), so that a certain degree of skepticism is necessary for historical papers unless cell line authentication is described. The loss of KU7 as a model for testing intravesical drug delivery has left a significant gap in our modeling ability.…”
Section: Discussionmentioning
confidence: 90%